2015
DOI: 10.1352/1944-7558-120.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Long-Term Growth Hormone Treatment on Adaptive Functioning in Infants With Prader-Willi Syndrome

Abstract: The aim of this study was to investigate the effect of growth hormone treatment on adaptive functioning in children with Prader-Willi syndrome. Vineland Adaptive Behavior Scale (VABS) was assessed during a randomized controlled trial (RCT) and after 7 years of growth hormone treatment. In the RCT, 75 children (42 infants and 33 prepubertal children) with Prader-Willi syndrome were included. Subsequently, 53 children were treated with long-term growth hormone. Our study demonstrates a marked delay in adaptive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The developmental window of rapid synapse formation and network connectivity in the first few years of life may perhaps be the best time to deliver a beneficial treatment 23,25,29 . The first 5 years of life is also a time of low serotonin production in the frontal cortex in children with ASD 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developmental window of rapid synapse formation and network connectivity in the first few years of life may perhaps be the best time to deliver a beneficial treatment 23,25,29 . The first 5 years of life is also a time of low serotonin production in the frontal cortex in children with ASD 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that treatment in young children with neurodevelopmental problems may have the best effects because the brain is still rapidly developing and thus most susceptible to intervention 2327 . For example, there was no effect in adolescents and adults with FXS treated with arbaclofen, but children ages 5 to 11 years demonstrated benefit in several behavioral measures 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment with rGH improves growth and body composition resulting in better motor strength and function. Additional benefits include more favorable lipid profiles, positive effects on development and cognition, and improved depressive symptoms (Bakker, Kuppens, et al, ; Dykens, Roof, & Hunt‐Hawkins, ; Lo et al, ). Contraindications to use include severe obesity, untreated severe obstructive sleep apnea (OSA), uncontrolled diabetes, active malignancy, and active psychosis.…”
Section: Clinical Managementmentioning
confidence: 99%
“…Developmental milestones may be reached at an earlier age and mental development and adaptive skills may be improved [13,14]. However, in most GH studies reported to date very few children were less than 1 year old when GHT was started and were grouped together in the analysis with toddlers [14,15] or 3 to 4 year old children [16,17].…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Despite the documented benefits of early initiation of GHT in PWS [6,14,16], there may be some hesitation to commence GHT in very young children because of the wide array of difficulties in infancy and the paucity of publications on the optimal dose and time to commence as well as safety, for example with respect to upper airway compromise secondary to lymphoid ACCEPTED MANUSCRIPT…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%